Woman Does not Exist: Lacan, Poe and Re-(W)righting the Feminine - Khan, Sheheryar (Journal of Research in Humanities, 2023)
For Lacan, in a social order characterized by the Law of the Father, women’s identity is erased and they have to appropriate themselves according to the idea of the ‘feminine’ as conceived by masculine phantasmatic economy. This cultural ‘reconstruction’ of a woman’s self is carried thorough a rigid process of mortification that turns women into an ‘object’ of knowledge, left to be reconstituted and reformulated. Literature is one such site where this textual reconstruction takes place and where this idea of ‘The Woman’ is raised to the level of a cultural fantasy. This essay interprets three short stories “Ligeia”, “The Oval Portrait” and “Morella” by Edgar Allan Poe to demonstrate how the female self is obliterated and her identity reconstituted to fit into masculine fantasy framework. All three stories have male narrators and the women characters die at the end and the essay contends that this death should be read as the symbolic extinction of female self to morph her into the male idea of the ‘feminine’.